Investigation Mechanical Characterization of Rattan Under Chemical Treatment - Yahaya, Ammar; Mahzan, Shahruddin (Research Progress in Mechanical and Manufacturing Engineering, 2022)
This research is conducted to discover the comparison of the rattan condition before and after treatment is applied. Efficient design of any structural component and the strength capabilities of the material to be utilized must be known ahead of time. Rattan cane offers a challenge due to the quality that cannot be controlled as it is a naturally occurring material. All of the other structural materials are man-made, and some form of quality control can be conducted during their manufacturing. This has resulted in some scientific work on the structural qualities of rattan cane. The study was concentrated on one of the features of rattan rods by examining the effects of rattan rod moisture content during or after modifications or treatments. In which have been structurally coated with mechanical parameters such as the tensile strength on the surface of the rattan rod. The rattan was implemented after the treatment in the shape of a finishing product to see its reliability and durability compared to the other material product in the market.